H
huy14112
Ta có:
[TEX]A.\frac{1}{13}=\frac{A}{13}=\frac{13^{19}+1}{(13^{18}+1).13}=\frac{13^{19}+1}{13^{19}+13}[/TEX]
Làm tương tự với B
Ta sẽ được:
[TEX]\frac{A}{13}=\frac{13^{19}+1}{13^{19}+13}[/TEX]
[TEX]\frac{B}{13}=\frac{13^{20}+1}{13^{20}+13}[/TEX]
Ta có:
[TEX]1-\frac{A}{13}=\frac{12}{13^{19}+13}[/TEX]
[TEX]1-\frac{B}{13}=\frac{12}{13^{20}+13}[/TEX]
mà
[TEX]\frac{12}{13^{20}+13} < \frac{12}{13^{19}+13}[/TEX]
[TEX]\Rightarrow \frac{B}{13} > \frac{A}{13}[/TEX]
[TEX]\Rightarrow B>A[/TEX]
[TEX]A.\frac{1}{13}=\frac{A}{13}=\frac{13^{19}+1}{(13^{18}+1).13}=\frac{13^{19}+1}{13^{19}+13}[/TEX]
Làm tương tự với B
Ta sẽ được:
[TEX]\frac{A}{13}=\frac{13^{19}+1}{13^{19}+13}[/TEX]
[TEX]\frac{B}{13}=\frac{13^{20}+1}{13^{20}+13}[/TEX]
Ta có:
[TEX]1-\frac{A}{13}=\frac{12}{13^{19}+13}[/TEX]
[TEX]1-\frac{B}{13}=\frac{12}{13^{20}+13}[/TEX]
mà
[TEX]\frac{12}{13^{20}+13} < \frac{12}{13^{19}+13}[/TEX]
[TEX]\Rightarrow \frac{B}{13} > \frac{A}{13}[/TEX]
[TEX]\Rightarrow B>A[/TEX]